2019
DOI: 10.1109/tasc.2019.2908241
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Coated Conductors Fabricated by UTOC-MOD Process

Abstract: A new metal organic deposition (MOD) process using precursor solution containing metal trifluoroacetates was developed to improve in-field performance. In this process, the pinning centers of BaMO 3 (M: metal elements such as Zr and Hf) materials could be made to be finer by reducing the once coating thickness in the coating and calcination step. This is referred to as the ultrathin once coating (UTOC)-MOD process. This process improves the in-field performance. The UTOC-MOD process also has the advantage of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The main consequence of this reduced ratio is that the YBCO growth temperature is decreased and the superconducting properties improved due to the modified microstructure [31,53,57,[74][75][76][77]. Microstructural studies have shown that these non-stoichiometric compounds display a reduced porosity and a lower concentration of a/b nucleated crystals while the expected secondary phases (mainly Y 2 Cu 2 O 5 and CuO) do not perturb in a relevant way the epitaxial microstructure and so this modified metal stoichiometry has been widely used by many authors to grow CCs displaying very good superconducting performance [57,74,76,[78][79][80][81]. It is also worth to mention that the validity of the TFA approach has been widely proved for most of the Rare Earth compounds in REBCO films where high superconducting performances have been demonstrated [40,73,82].…”
Section: Low Fluorine Solution Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The main consequence of this reduced ratio is that the YBCO growth temperature is decreased and the superconducting properties improved due to the modified microstructure [31,53,57,[74][75][76][77]. Microstructural studies have shown that these non-stoichiometric compounds display a reduced porosity and a lower concentration of a/b nucleated crystals while the expected secondary phases (mainly Y 2 Cu 2 O 5 and CuO) do not perturb in a relevant way the epitaxial microstructure and so this modified metal stoichiometry has been widely used by many authors to grow CCs displaying very good superconducting performance [57,74,76,[78][79][80][81]. It is also worth to mention that the validity of the TFA approach has been widely proved for most of the Rare Earth compounds in REBCO films where high superconducting performances have been demonstrated [40,73,82].…”
Section: Low Fluorine Solution Synthesismentioning
confidence: 99%
“…It was shown that above a concentration of 10%-12% mol in the final YBCO layer there was a tendency towards NP aggregation and the size control of the NPs was compromised [90,91]. An alternative deposition approach was devised which hindered the NP diffusion and coarsening by taking advantage of the CuO interlayer formed at the intersurfaces of multideposited pyrolyzed films, called UTOC [40,[79][80][81]. This novel process selects ultrathin (∼30 nm) YBCO layers and a solution multideposition approach to reach competitive total film thickness and critical currents, for instance, 35 repetitions of the spin-coating/pyrolysis cycle were required to get a final film thickness of ∼0.6-0.7 µm [40,92].…”
Section: Np Preparation and Colloidal Solution Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modification is motivated by the reports of conductor damage caused by locally reduced critical current leading to hot spot creation [30][31][32][33][34][35]. It is well documented that the electric current in thin high-T c layer should avoid local imperfections [36][37][38][39][40][41][42][43][44]. Because of a highly nonlinear rise of voltage with current, the regions with lowest critical current would form hot spots, coexisting with the neighboring superconducting regions [45].…”
Section: Introductionmentioning
confidence: 99%